2000
DOI: 10.1002/(sici)1099-1085(200001)14:1<145::aid-hyp916>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The water balance of the Dead Sea: an integrated approach

Abstract: Abstract:The Dead Sea is the lowest spot on Earth. It is a closed saline lake located in the middle of the Jordan Rift Valley between Lake Tiberias and the Red Sea. Its major tributaries are the Jordan River itself and the Dead Sea side wadis. The Dead Sea has a unique ecosystem and its water has curative, industrial and recreational signi®cance. The level of the Dead Sea has been continuously falling since the early 1930s at an average rate of 0 . 7 m per year. The water level, as of February 1998, is about 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 3 publications
(6 reference statements)
1
7
3
Order By: Relevance
“…Recent studies showed that Dead Sea evaporation rate varied from 1.05 to 2.0 m/year for the current salinity (Stanhill [31]; Alpert et al [32]; Salameh and El-Naser [16] and Lensky et al [33]). These values which based on water and heat balance calculations were in contrary with other studies that estimated the evaporation rate at the Dead Sea from 1.30 to 1.54 m (Al-Weshah, [34]).…”
Section: Dead Sea -Red Sea Water Mixing Experimental Site and Samplingcontrasting
confidence: 99%
“…Recent studies showed that Dead Sea evaporation rate varied from 1.05 to 2.0 m/year for the current salinity (Stanhill [31]; Alpert et al [32]; Salameh and El-Naser [16] and Lensky et al [33]). These values which based on water and heat balance calculations were in contrary with other studies that estimated the evaporation rate at the Dead Sea from 1.30 to 1.54 m (Al-Weshah, [34]).…”
Section: Dead Sea -Red Sea Water Mixing Experimental Site and Samplingcontrasting
confidence: 99%
“…The base flows that we measured during the drought years of 2000–2001 (500–1100 L s −1 ) are about 40 times lower than the historical flow rates. These discharge values are even lower than recent published estimates (e.g., Al‐Washah, 2000). While the intensive water use by the regional countries is responsible for the general discharge decrease, drought conditions reduce it further, resulting in local drying events.…”
Section: Resultscontrasting
confidence: 68%
“…Before the 1950s the Dead Sea had received about 1,300 million cubic meters per year (MCM/year) of good quality freshwater from its major contributor, the Jordan River. Until the late 1990s, however, this amount has dropped to about 100-200 MCM/year of saline and polluted water Al-Weshah, 2000;Shavit et al, 2001). The reasons for this development are given in Figure 1: Israel had used nearly the entire inflow into the Lake Tiberias for use in the National Water Carrier.…”
Section: Discussionmentioning
confidence: 99%